Eksistensi Provost Satuan Polisi Pamong Praja di Daerah - Dida Suhada (Research and Development Agency Ministry of Home Affairs, 2017)
Provost is usually found on military based institution, but the provost also be found in the Civil Service Police Unit, Satpol PP Provost in carrying out its duties and functions in the monitoring and implementation of development activities at the State Civil Administrative Region Government and its members. The purpose of this study was to determine the extent of the presence of Provost Civil Service Police Unit reviewed from a legal perspective of the Minister of Home Affair Regulation Number 19 Year 2013 on Guidelines for Office Clothing, Supplies And Equipment Operations Civil Service Police Unit. The study used a qualitative research approach normative qualitative descriptive analysis. Secondary and primary data obtained by the study of literature and interviews and observations. The conclusion from this study is that the legal basis for the establishment of the Provost at the municipal police are not in accordance with the Regulation of the Minister of Home Affair Number 19 Year 2013 on Guidelines for Office Clothing, Supplies And Equipment Operations Civil Service Police Unit. The formation only by Decision of the Head municipal police and Decision of the Regional Secretary. Besides recruiting and training members of municipal police Provost also not based on the expertise of the investigation.